2022
DOI: 10.20473/jr.v8-i.3.2022.140-146
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline Correlation to QT Interval Prolongation in DR-TB Patients

Abstract: Introduction: Drug-Resistant Tuberculosis (DR-TB) requires adequate treatment. Bedaquiline is a priority medicine in the treatment regimen of DR-TB. One of the adverse events is QT interval prolongation, which can increase the risk of torsade de pointes (TdP) and lead to death. DR-TB patient screening before starting the treatment and monitoring QT interval during the treatment should be performed. This study aimed to determine Bedaquiline correlation to QT interval prolongation in DR-TB patients. Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The administration of bedaquiline and or delamanid as part of an all-oral regimen improve success treatment (culture conversion) and minimize side effects, such as hearing loss, hearing disorders, and renal dysfunction, related to the second line injectable drugs (Yang et al, 2017). Several studies have reported that adding bedaquiline and or delamanid to DR-TB regimens effectively increase a culture conversion rate at 6 months or after treatment completion (Kempker et al, 2020;Maretbayeva et al, 2021) Regimens containing bedaquiline to treat DR-TB is relatively safe with no cases of QTc interval more than 500 ms during six months of treatment as reported by Primadana et al (Primadana et al, 2022). On the other hand, beyond its bactericidal activity, delamanid alter the function of host immune cell.…”
Section: Discussionmentioning
confidence: 92%
“…The administration of bedaquiline and or delamanid as part of an all-oral regimen improve success treatment (culture conversion) and minimize side effects, such as hearing loss, hearing disorders, and renal dysfunction, related to the second line injectable drugs (Yang et al, 2017). Several studies have reported that adding bedaquiline and or delamanid to DR-TB regimens effectively increase a culture conversion rate at 6 months or after treatment completion (Kempker et al, 2020;Maretbayeva et al, 2021) Regimens containing bedaquiline to treat DR-TB is relatively safe with no cases of QTc interval more than 500 ms during six months of treatment as reported by Primadana et al (Primadana et al, 2022). On the other hand, beyond its bactericidal activity, delamanid alter the function of host immune cell.…”
Section: Discussionmentioning
confidence: 92%
“…The mean QT interval value after treatment with Bedaquiline in each article was rated as safe at <450ms. Only one article by Vandu et al 12 , 2022 which in their research found a mean QT interval value of 458.4ms, this according to the degree of QT interval display is considered as QT prolongation degree 1. When looking at the column of QT Interval changes from baseline also in each study can be said to be safe, no study found a mean increase in QT interval from baseline ≥60ms.…”
Section: Qt Interval Changes In the Use Of Bedaquilinementioning
confidence: 99%